Design of a coumarinyl-picolinoyl hydrazide Schiff base for the fluorescence turn-on–off sequential sensing of Al3+ and nitroaromatics, and electronic device fabrication. (6th September 2019) - Purkait, Rakesh; Dey, Arka; Dey, Sunanda; Ray, Partha Pratim; Sinha, Chittaranjan
Abstract : Designing a small organic molecule for fluorescence sensing and electrical conductivity is a challenging task. Abstract : ( E )- N ′-((7-Hydroxy-4-methyl-2-oxo-2 H -chromen-8-yl)methylene)picolinohydrazide (H-CPh ), a greenish yellow emitter in the solid state, aggregates in DMSO solution upon increasing the percentage of water (>50%) and the maximized emission intensity was reached at 90% water–DMSO medium. Upon excitation at 400 nm in pure aquatic medium (HEPES buffer, pH 7.2) H-CPh shows fluorescence sensitivity to Al 3+ ( λ em, 470 nm) and forms a 1 : 1 complex, [(CPh)Al(OH)(H2 O)]NO3, with a limit of detection (LOD) of 6.99 nM. The complex, [(CPh)Al(OH)(H2 O)]NO3 shows sensitivity to nitroaromatics by quenching the strong emission of the fluorogenic complex and the LODs are: 2, 4-dinitrophenol (DNP), 1.67 μM and 2, 4, 6-trinitrophenol (TNP) 0.99 μM. The H-CPh is electronically a semiconductor and the experimental (2.78 eV) and the DFT derived (2.75 eV) band gaps are comparable. The H-CPh forms a Schottky diode and its photoconductivity (19.98 × 10 −4 S m −1 ) is three times higher than the dark phase conductivity (6.42 × 10 −4 S m −1 ).